New Information on the Hosts and Distribution of the Marine Fish Leeches Trachelobdella lubrica and Pontobdella muricata (Clitellata, Hirudinida) - Oktener, A.; Utevsky, S.Yu. (Вестник зоологии, 2010)
Fish leeches collected in the Aegean Sea, the Sea of Marmara and the Black Sea were examined. Trachelobdella lubrica (Grube, 1840) was recorded for the first time from the ballan wrasse Labrus bergylta (Osteichthyes, Labridae), marine bream Diplodus vulgaris (Osteichthyes, Sparidae) and the grouper Epinephelus aeneus (Osteichthyes, Serranidae) from aquiculture. The leeches of this species were found in the Aegean Sea and the Sea of Marmara on the body surface, in the mouth and gill cavities of their hosts. Leeches identified as Pontobdella muricata (Linnaeus, 1758) were collected from the thornback ray Raja clavata (Chondrichthyes, Rajidae) in the Black Sea.